Mismatch repair, p53, and L1 cell adhesion molecule status influence the response to chemotherapy in advanced and recurrent endometrial cancer - Jung Chul Kim; Byungsoo Ahn; Yong Jae Lee; Eun Ji Nam; Sang Wun Kim; Sunghoon Kim; Young Tae Kim; Eunhyang Park; Jung-Yun Lee (BMC Cancer)
Abstract Objective This study aimed to identify the recurrence and survival rates according to the mismatch repair (MMR), p53, and L1 cell adhesion molecule (L1CAM) status in patients with advanced and recurrent endometrial cancer (EC) receiving systemic chemotherapy. Methods This single-center retrospective cohort study included chemotherapy-naïve patients with advanced-stage (III/IV) or recurrent EC between January 2015 and June 2022 (n = 156), who were administered chemotherapy as adjuvant therapy or first-line palliative treatment. MMR and p53 status were assessed, and L1CAM was tested using immunohistochemistry in the p53-wild and MMR-proficient (p53wt/pMMR) group. The primary outcomes were progression-free survival (PFS) and overall survival (OS). Results Of the 156 patients, 62 (39.7%), 53 (34.0%), and 41 (26.3%) had p53wt/pMMR, abnormal p53 (p53abn), and MMR-deficient (dMMR) tumors, respectively. PFS and OS were longest in dMMR, followed by p53wt/pMMR, and were the least in p53abn tumors (PFS: p = 0.0006, OS: p = 0.0013). After p53wt/pMMR was classified according to positive or negative L1CAM status, the L1CAM negative group exhibited significantly shorter survival rates than the L1CAM positive group (PFS: p = 0.0001, OS: p = 0.0027). p53abn tumors were independent prognostic factors for poor PFS (PFS: p = 0.039 on multivariable analysis). Conclusion In chemotherapy-naïve patients with advanced and recurrent EC, there was a better prognosis in the order of MMR-D, p53wt/pMMR, and p53abn tumors after chemotherapy. L1CAM status is useful as a new marker to stratify p53wt/pMMR in advanced and recurrent groups.